2019
DOI: 10.1186/s40168-019-0753-z
|View full text |Cite
|
Sign up to set email alerts
|

The composition and functional protein subsystems of the human nasal microbiome in granulomatosis with polyangiitis: a pilot study

Abstract: BackgroundEar, nose and throat involvement in granulomatosis with polyangiitis (GPA) is frequently the initial disease manifestation. Previous investigations have observed a higher prevalence of Staphylococcus aureus in patients with GPA, and chronic nasal carriage has been linked with an increased risk of disease relapse. In this cross-sectional study, we investigated changes in the nasal microbiota including a detailed analysis of Staphylococcus spp. by shotgun metagenomics in patients with active and inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…GWAS has also indicated that EGPA may be two distinct diseases based on ANCA status, with ANCA negative disease distinct from AAV. Metagenomic sequencing of nasal swabs has confirmed an association between nasal microbiome dysbiosis and disease activity in GPA; disease activity is associated with S aureus predominance, compared with S epidermidis in quiescent disease and controls 89 . High lifetime silica exposure has been associated with an increased risk of developing AAV 90 which, combined with the typical early respiratory tract involvement, raises of the possibility of other inhaled environmental triggers in the disease.…”
Section: Advances and Future Directionsmentioning
confidence: 93%
See 1 more Smart Citation
“…GWAS has also indicated that EGPA may be two distinct diseases based on ANCA status, with ANCA negative disease distinct from AAV. Metagenomic sequencing of nasal swabs has confirmed an association between nasal microbiome dysbiosis and disease activity in GPA; disease activity is associated with S aureus predominance, compared with S epidermidis in quiescent disease and controls 89 . High lifetime silica exposure has been associated with an increased risk of developing AAV 90 which, combined with the typical early respiratory tract involvement, raises of the possibility of other inhaled environmental triggers in the disease.…”
Section: Advances and Future Directionsmentioning
confidence: 93%
“…Metagenomic sequencing of nasal swabs has confirmed an association between nasal microbiome dysbiosis and disease activity in GPA; disease activity is associated with S aureus predominance, compared with S epidermidis in quiescent disease and controls. 89 High lifetime silica exposure has been associated with an increased risk of developing AAV 90 in EGPA. Rituximab is replacing conventional therapy as both a remission-induction and maintenance agent [92][93][94][95] and has also shown benefit in the specific management of head and neck manifestations of GPA.…”
Section: Advan Ce S and Future D Irec Ti On Smentioning
confidence: 99%
“…Esp-secreting S. epidermidis correlates with the absence of S. aureus [36] or secretion of hydrogen peroxide by Streptococcus pneumoniae [37] ), whereas indirect competition may be related to modified living conditions or competition for nutrients [38] . In our pilot study investigating the nasal microbiome in patients with GPA, we found that in most cases with presence of Staphylococcus pseudintermedius the antagonistic relationship between S. aureus and S. epidermidis is broken, indicating that all three occupy the same niche [39] .…”
Section: The (Healthy) Nasal Microbiome and Influences On Diversitymentioning
confidence: 88%
“…Indeed, the AR patients' bNM was less rich in terms of residential bacteria and associated with a reduced bacterial phylogenetic diversity compared to the HS group. Interestingly, reduced diversity in the bNM was identi ed also in other respiratory diseases such as in patients with Chronic Rhinosinusitis (CRS) [56,57], in patients with asthma [58], and in patients affected by granulomatosis with polyangiitis [59]. The importance of a diverse microbiota has been widely documented as pivotal in maintaining the mucosa integrity and an effective immune system [16,45,60].…”
Section: Discussionmentioning
confidence: 99%